Maintenance of Implant Patients: A Narrative Review. Issue 2 (April 2019) - Kelekis-Cholakis, Anastasia; Rothney, Janet
Abstract : Purpose: Patient-administered and professionally administered periimplant maintenance have been recommended to ensure long-term periimplant tissue health. In this narrative review, the effectiveness of patient and professionally administered interventions and the current level of evidence that periimplant maintenance therapy is effective in preventing the occurrence of periimplant disease were examined. Materials and Methods: A systematic literature search was performed in Ovid MEDLINE, EMBASE, Cochrane Library, and Web of Science, for evidence-based articles in support of the above topics. Results: Twenty-six clinical trials were included and stratified into categories based on topics. Conclusions: The following conclusions were reached: (a) mechanical plaque removal is the foundation of successful periimplant therapy; (b) patient- and professionally administered plaque control has been shown to reduce periimplant inflammation, although complete resolution of inflammation is not always evident; (c) the use of adjunctive chemical agents in maintaining periimplant health still remains to be determined; and (d) regular periimplant maintenance plays a significant role in maintaining periimplant soft and hard tissue health.